Case Report: A Relatively Mild Presentation of Unilateral Congenital Pulmonary Lymphangiectasia - Adair, Dionne; Rabah, Raja; Ladino-Torres, Maria; Saba, Thomas G. (Frontiers in Pediatrics, 2021)
Pulmonary lymphangiectasia (PL) is a rare congenital disorder of pulmonary lymphatic development. Although it was traditionally a fatal disorder of infancy, some cases in later childhood have been reported, suggesting a spectrum of severity. We present an unusual case of unilateral, congenital pulmonary lymphangiectasia. Our patient presented with neonatal respiratory distress, a chronic wet cough and recurrent episodes of bronchitis. Chest CT revealed thickening of the interlobular septae of the right lung. A lung biopsy confirmed the diagnosis of lymphangiectasia. His clinical course is characterized by chronic coughing and recurrent bronchitis but normal growth and development. This case illustrates a relatively mild presentation of unilateral PL, which, along with other reports, suggests variability in the presentation and severity of this disorder. In the absence of imaging and histological examination, mild presentations may go undiagnosed.